IMPACT OF OBESITY AND DIABETES MELLITUS TYPE II WITH INCIDENCE OF HYPERTENSION IN AGE 45-65 YEARS OLD - Tiara Syamsa Noor Wildania; Shofa Nur Fauzah; Dini Sapardini Warsodoedi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Hypertension is one of the main causes of mortality and morbidity in Indonesia. Hypertension is also the third biggest risk factor for early deaths. Several previous researches have shown that obesity and diabetes mellitus type II (DM type II) are the factors in the occurrence of hypertension. Previous research did not include the stage of obesity and DM type II, by this reason the research was aimed to analyze the correlation between the stage of obesity and stage of DM type II with hypertension.Methodology: This research used observational analytic with cross-sectional design. This study involved 161 patients who were selected by consecutive sampling method. The inclusion criteria of the sample were aged 45-60 years old, obese, and have been diagnosed of DM type II and hypertension in Waled Regional General Hospital.Results: The result revealed that stage of obesity and stage of DM type II were significantly associated with hypertension (p<001, p<01, respectively). Other variables that also significantly associated with hypertension were age and gender. Conclusion: There was the strong correlation between stage of obesity and hypertension. Public health policy maker may promote to prevent the obesity in order to decrease the incidence of hypertension.